Editorial: A Golden Anniversary - Belanger, G. Maurice (Canadian Journal of Optometry, 2026)
As of May, 1989, The Canadian Journal of Optometry * La Revue canadienne d'optometrie celebrates the 50th anniversary of lssue Number I. Yes, it was in May, 1939 that The Canadianlournal of Optometry, sponsored then by the Board of Examiners in Optometry for the Province of Ontario, first saw the light of day under the watchful eye of Edward Bind.